UEFA injury study: a prospective study of hip and groin injuries in professional football over seven consecutive seasons - Werner, J.; Hägglund, M.; Walden, M.; Ekstrand, J. (British Journal of Sports Medicine, 2009)
Background: Groin injury is a common injury in football and a complicated area when it comes to diagnosis and therapy. There is a lack of comprehensive epidemiological data on groin injuries in professional football.